Invasive Group B Streptococcus Disease With Recurrence and in Multiples: Towards a Better Understanding of GBS Late-Onset Sepsis - Freudenhammer, Mirjam; Karampatsas, Konstantinos; Le Doare, Kirsty; Lander, Fabian; Armann, Jakob; Acero Moreno, Daniel; Boyle, Margaret; Buxmann, Horst; Campbell, Ruth; Chalker, Victoria; Cunney, Robert; Doherty, Lorraine; et al. (Frontiers in Immunology, 2021)
Group B Streptococcus (GBS) is a common intestinal colonizer during the neonatal period, but also may cause late-onset sepsis or meningitis in up to 0.5% of otherwise healthy colonized infants after day 3 of life. Transmission routes and risk factors of this late-onset form of invasive GBS disease (iGBS) are not fully understood. Cases of iGBS with recurrence (n=25) and those occurring in parallel in twins/triplets (n=32) from the UK and Ireland (national surveillance study 2014/15) and from Germany and Switzerland (retrospective case collection) were analyzed to unravel shared (in affected multiples) or fixed (in recurrent disease) risk factors for GBS disease. The risk of iGBS among infants from multiple births was high (17%), if one infant had already developed GBS disease. The interval of onset of iGBS between siblings was 4.5 days and in recurrent cases 12.5 days. Disturbances of the individual microbiome, including persistence of infectious foci are suggested e.g. by high usage of perinatal antibiotics in mothers of affected multiples, and by the association of an increased risk of recurrence with a short term of antibiotics (aOR 4.2 (1.3-14.2), P=0.02). Identical GBS strains serotypes in both recurrent infections and concurrently infected multiples might indicate a failed microbiome integration of GBS strains that are generally regarded as commensals in healthy infants. The dynamics of recurrent GBS infections or concurrent infections in multiples suggest individual patterns of exposure and fluctuations in host immunity, causing failure of natural niche occupation.